INTRODUCTION TO ANTHROPOLOGY - Zaenuddin Hudi Prasojo; Reviewed by: Aspari Ismail (Graduate Program of Pontianak Institute of Islamic Studies, 2013)
Anthropology is the study of mankind (anthropos). Etymologically, anthropology comes from the word anthropos meaning man and logos meaning knowledge. Anthropology looks at humans as something complex in terms of physical, emotional, social, and cultural complexity. Anthropology also refers to the science of humans and their culture.